2019
DOI: 10.2174/1381612825666190110161843
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Targeting Angiogenesis as a Potential Therapeutic Approach in the Treatment of Colorectal Cancers

Abstract: Angiogenesis refers to the formation of recent blood vessels, which is one of the characteristics of cancer progression and it has been deliberated as a putative target to the treatment of many kinds of cancers. The VEGF signaling substrate is very important for angiogenesis and is commonly high-regulated in tumors. As a result, this molecule has attracted the attention of most of the researchers to develop antiangiogenic therapies. We have presented that VEGF blockage in neoadjuvant setting via bevacizumab, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The importance of miRNAs in prognosis, diagnosis, and treatment as well as drug resistance of GI cancer has been widely reported. [14][15][16][17] Recently, accumulating evidence has indicated that a variety of miRNAs could target CD molecules in GI cancers, thereby modulating the cancer progression. Using the Gene Expression Omnibus database and RNA-Seq colon cancer data from The Cancer Genome Atlas data portal, Gao et al 18 reported that CD92 was targeted by miR-183, miR-206, and miR-147 in colon cancer, and differentially expressed genes (DEGs) were identified between colon tumor samples and adjacent normal samples.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of miRNAs in prognosis, diagnosis, and treatment as well as drug resistance of GI cancer has been widely reported. [14][15][16][17] Recently, accumulating evidence has indicated that a variety of miRNAs could target CD molecules in GI cancers, thereby modulating the cancer progression. Using the Gene Expression Omnibus database and RNA-Seq colon cancer data from The Cancer Genome Atlas data portal, Gao et al 18 reported that CD92 was targeted by miR-183, miR-206, and miR-147 in colon cancer, and differentially expressed genes (DEGs) were identified between colon tumor samples and adjacent normal samples.…”
Section: Introductionmentioning
confidence: 99%
“…7 In particular, certain miRNAs function as pro-angiogenic regulators. [8][9][10] Among them, miR-126, which is specifically expressed in endothelial cells, may be the most important and acts as a key regulator in promoting angiogenesis as well as maintaining vascular integrity. For instance, up-regulation of miR-126 can contribute to angiogenesis after vessel injury or hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have shown the interaction of miRNAs with other biomarkers, such as KRAS [ 89 , 90 ], and their consequent role in predicting treatment response to classical cytotoxic chemotherapy or targeted therapy (anti-epidermal growth factor receptor (EGFR) and anti-VEGF) [ 91 , 92 , 93 , 94 ].…”
Section: Micrornamentioning
confidence: 99%
“…Activating mutations in the RAS genes occur in approximately 45% of CRC. Among them, the KRAS mutation is mainly involved in preventing the hydrolysis of the GTP complex, leading to cell Recently, some studies have shown the interaction of miRNAs with other biomarkers, such as KRAS [89,90], and their consequent role in predicting treatment response to classical cytotoxic chemotherapy or targeted therapy (anti-epidermal growth factor receptor (EGFR) and anti-VEGF) [91][92][93][94].…”
Section: Krasmentioning
confidence: 99%